2012
DOI: 10.1371/journal.pbio.1001290
|View full text |Cite
|
Sign up to set email alerts
|

Mediator Acts Upstream of the Transcriptional Activator Gal4

Abstract: We show that Mediator, a protein originally isolated on the basis of its ability to respond to transcriptional activators, and thought to be regulated by an activator, can also be the master that controls the activator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Intriguingly, the recruitment of TBP and RNA polymerase II to the promoter during GAL sense transcription is facilitated by the proteasome (1,2,49,92). Such regulation has recently been attributed to occur via degradation of Gal80p (92), which specifically controls GAL1-GAL10 sense transcription (60,61,(68)(69)(70)(71). However, our RT-PCR analysis revealed that, unlike its sense transcription, GAL10 antisense transcription in dextrose-containing growth medium was not regulated by the proteasome (Fig.…”
Section: Fig 4 Rna Polymerase II Is Essential For Gal10 Antisense Tramentioning
confidence: 72%
See 1 more Smart Citation
“…Intriguingly, the recruitment of TBP and RNA polymerase II to the promoter during GAL sense transcription is facilitated by the proteasome (1,2,49,92). Such regulation has recently been attributed to occur via degradation of Gal80p (92), which specifically controls GAL1-GAL10 sense transcription (60,61,(68)(69)(70)(71). However, our RT-PCR analysis revealed that, unlike its sense transcription, GAL10 antisense transcription in dextrose-containing growth medium was not regulated by the proteasome (Fig.…”
Section: Fig 4 Rna Polymerase II Is Essential For Gal10 Antisense Tramentioning
confidence: 72%
“…Collectively, our data support the idea that TBP promotes the targeting of RNA polymerase II for antisense transcription. Intriguingly, the recruitment of TBP and RNA polymerase II to the promoter during GAL sense transcription is facilitated by the proteasome (1,2,49,92). Such regulation has recently been attributed to occur via degradation of Gal80p (92), which specifically controls GAL1-GAL10 sense transcription (60,61,(68)(69)(70)(71).…”
Section: Fig 4 Rna Polymerase II Is Essential For Gal10 Antisense Tramentioning
confidence: 99%
“…Transcriptional complexes such as the mediator are able to orchestrate their own recruitment to the GAL promoter and act upstream of their recruiter, Gal4, in response to Snf1-conveyed signals, by controlling the E3 ligase SCF Mdm30 -mediated ubiquitination and subsequent proteasomal degradation of Gal80 (Ang et al ., 2012 ). Gal4 monoubiquitination, initially thought to destabilize this transcription factor, seems to serve instead as protective mechanism against the promoter-stripping proteasome ATPases (Archer et al ., 2008 ).…”
Section: Specific Nutrient Signaling Pathways: Triggered By a Single mentioning
confidence: 99%
“…This result contrasts with our report that Cdc48 stimulates the activity of the yeast activator Gal4 ( Bonizec et al ., 2014 ). To confirm that Gcn4 and Gal4 are affected differently by the cdc48-3 mutation, we examined Gal4 activity in the cdc48-3 mutant strain; we also examined the effect of GAL80 deletion in this context, which has been argued to be a point of Gal4 regulation by the UPS ( Ang et al ., 2012 ). Supporting our previous study ( Bonizec et al ., 2014 ), mutation of Cdc48 reduced activation of the GAL10 locus ( Figure 4H ), whereas the GAL80 deletion did not affect the sensitivity of GAL10 transcription to the cdc48 -3 mutation.…”
Section: Resultsmentioning
confidence: 99%